Architecture and key technology of telco edge cloud - Qiao FU; Xiaodong DUAN; Lu WANG; Yamei FAN (Dianxin kexue)
With the increased requirement for low latency,high bandwidth and artificial intelligence for future network,the concept of edge cloud,which could bring network service closer to end users,has become a hot topic recently.For now,the understanding and study on edge cloud is still at the startup phase,with no end-to-end framework and solution yet.Combining with the network transformation requirement for the telco network,and the newly emerging edge service,a typical framework and multiple key features were proposed.And the possible solutions for edge cloud related technologies was provided to try to bring insight for the future edge cloud development.